If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 4x + 6 Reorder the terms: 7 + 3x = 4x + 6 Reorder the terms: 7 + 3x = 6 + 4x Solving 7 + 3x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + 3x + -4x = 6 + 4x + -4x Combine like terms: 3x + -4x = -1x 7 + -1x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + -1x = 6 + 0 7 + -1x = 6 Add '-7' to each side of the equation. 7 + -7 + -1x = 6 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 6 + -7 -1x = 6 + -7 Combine like terms: 6 + -7 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| g+-5=27 | | 5c-7=17 | | 5-x/8=10 | | g+-5=12 | | 19=5n+-3n | | -3(b-2)= | | x^2-7x+5/4=0 | | 2(3x+5)=4 | | 1/3m^2=-1/6m+1/2 | | 14+8x=6x-20+2x | | 4(x+3)=400 | | x-3/7=5/7 | | 3/2m=1/2 | | 0.09-15=5 | | 2.7y=y+1+1 | | 5x^2+5x-18=0 | | R-15=6 | | -6y=8-9+6y | | 2x+5y=-16 | | -2/5+x=2/5 | | 2.7y=1+1 | | 5s-1=6s | | x/3-1=5 | | z/3+7=9,5 | | -3y+2=8 | | 5/6a=5/8 | | -33-2=7-7x | | 7x+9-10x=-18 | | 3+2x=75 | | 2x+1y=1.70 | | 1/x+2/x+1 | | 3x-6=-9+25 |